Effects of Fertilization, Variety and Season on Fall Armyworm Attack on Bio-fortified Maize Production in the Kisangani Eco-region (Democratic Republic of the Congo) - D. Bangambingo; B.D. Nawelze; O. Mubenga; A.K. Lubobo; C.L. Inkoto; K.N. Ngbolua; G. Monde (Budapest International Research and Critics University, 2022)
Faced with soil impoverishment and irregular rainfall caused by climate change, a study has been initiated on the cultivation of bio-fortified maize in Kisangani in the Northeast of the Democratic Republic of the Congo. The study aimed at evaluating fertilization effects, new bio-fortified maize varieties and the season (Zea mays L) on production in the face of armyworm infestation. The split-plot experimental set-up was used, the first factor has been the variety and the second the fertilizers. The results have highlighted that the application of fertilizers at the sowing time does not significantly influence any production parameter. However, experimented maize varieties have differently behaved depending on seasons when the armyworm infestation.